Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Walker, Peter J.; Siddell, Stuart G.; Lefkowitz, Elliot J.; Mushegian, Arcady R.; Adriaenssens, Evelien M.; Alfenas-Zerbini, Poliane; Dempsey, Donald M.; Dutilh, Bas E.; García, María Laura; Curtis Hendrickson, R.; Junglen, Sandra; Krupovic, Mart; et al. (Archives of virology, 2022)
This article reports the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in March 2022. The entire ICTV was invited to vote on 174 taxonomic proposals approved by the ICTV Executive Committee at its annual meeting in July 2021. All proposals were ratified by an absolute majority of the ICTV members. Of note, the Study Groups have started to implement the new rule for uniform virus species naming that became effective in 2021 and mandates the binomial ‘Genus_name species_epithet’ format with or without Latinization. As a result of this ratification, the names of 6,481 virus species (more than 60 percent of all species names currently recognized by ICTV) now follow this format.